2011
DOI: 10.22610/imbr.v2i2.882
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Human Resources into Human Capital

Abstract: Human resource refers to the stock of productive skills and technical knowledge embodied in labor. It is tangible in nature. Many early economic theories refer to it simply as labor, one of the three factors of production, and consider it to be a fungible resource -- homogeneous and easily interchangeable. The goal of human resource management is to help an organization to meet strategic goals by attracting, and retaining employees and also to manage them effectively so that they deliver productive outputs. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…First, managers should have a shift in mindset: from the human resource to human capital where any expenditure on employees is regarded as an investment rather than an expense (Zakaria and Yusoff, 2011). If managers see employees merely as 'a resource', this could lead to the tendency that managers focus on exploiting only thatresource.…”
Section: New Trends In Human Resources Development Of Vietnamese Enterprisesmentioning
confidence: 99%
“…First, managers should have a shift in mindset: from the human resource to human capital where any expenditure on employees is regarded as an investment rather than an expense (Zakaria and Yusoff, 2011). If managers see employees merely as 'a resource', this could lead to the tendency that managers focus on exploiting only thatresource.…”
Section: New Trends In Human Resources Development Of Vietnamese Enterprisesmentioning
confidence: 99%
“…Human capital0can0be defined0as the total value of an organization's human resources (Zakaria, 2011;Kasmawati, 2017). The total value of human resources involves all staff in the organization and their ability to complete their work to succeed (Wang & Shieh, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Human capital has become one of the most important resources of organizations in the modern era, as business has shifted heavily toward the intangible assets, and hence the human resources become one of the most important strategic advantages for any organization (Zakaria, 2011). It is reported that individuals' performance is a function of both their abilities and their motivation, thus there is a great psychological impact on employees' performance, and that is why organizations seek to adapt the supportive policies and work environment to encourage their people and meet their needs and expectations (Restubog et al, 2010).…”
Section: Introductionmentioning
confidence: 99%